Case 3691: Cookeolus Fowler, 1928 (Osteichthyes: Priacanthidae): proposed conservation by designation of Priacanthus japonicus Cuvier, 1829 as the type species - Demirjian, Vahe D (Bulletin of Zoological Nomenclature)
Noticed BZN 72 (2) (30 June 2015): 108. Closed BZN 75 (31 December 2018): 302.